Comparative study between I-gel, a new supraglottic airway device, and classical laryngeal mask airway in anesthetized spontaneously ventilated patients - Helmy Amr (Saudi Journal of Anaesthesia, 2010)
Objective: To compare two different supraglottic airway devices, the laryngeal mask airway (LMA) and the I-gel, regarding easiness of insertion of the device, leak pressure, gastric insufflation, end tidal CO 2 , oxygen saturation, hemodynamic and postoperative complications in anesthetized, spontaneously ventilated adult patients performing different non-emergency surgical procedures. Materials and Methods: The study was carried out as a prospective, randomized, clinical trial among 80 patients who underwent different surgical procedures under general anesthesia with spontaneous ventilation in supine position. They were equally randomized into two groups: I-gel and LMA groups. Both the devices were compared with regard to heart rate, arterial BP, SPO 2 , end-tidal CO 2 , number and duration of insertion attempts, incidence of gastric insufflation, leak pressure and airway assessment after removal of the device. Results: No statistically significant difference was reported between both the groups, regarding heart rate, arterial BP, SPO 2 and end-tidal CO 2 . The mean duration of insertion attempts was 15.6±4.9 seconds in the I-gel group, while it was 26.2±17.7 seconds in the LMA group. The difference between both the groups regarding duration of insertion attempts was statistically significant (P=0.0023FNx01), while the number of insertion attempts was statistically insignificant between both the study groups (P>0.05). Leak pressure was (25.6±4.9 vs. 21.2±7.7 cm H 2 O) significantly higher among studied patients of the I-gel group (P=0.016FNx01) and the incidence of gastric insufflation was significantly more with LMA group 9 (22.5%) vs. I-gel group (5%) (P=0.016). Conclusion: Both LMA and I-gel do not cause any significant alteration in the hemodynamic status of the patients, end tidal CO 2 , and SPO 2 . The postoperative complications were not significantly different except nusea and vomiting was statistically significant higher in LMA group (P=0.032). among both LMA and I-gel patients. Insertion of I-gel was significantly easier and more rapid than insertion of LMA. Leak pressure was significantly higher with I-gel than LMA and thus incidence of gastric insufflation was significantly lower with I-gel.